Environnmantal defenders in colombia, and the abductive deduction in the struggle to access to justice [Defensores ambientales en colombia y razonamiento abductivo en el acceso a la justicia] (2020)
The objective of this paper is to analyze the right to access to justice for environmental defenders in Colombia through abduction, a mode of inference discovered by Charles Sanders Peirce philosopher. Under a qualitative methodological approach, the data analysis technique is “Discursive Analysis” and applied to sources (Colombian status, international law, and official documents) it helps to construct the right definition of environmental defender. However, the 9th article of the Agreement of Escazu provides a structured definition that could help the lack of precision in legal definitions narrowly related to environmental defender in Colombian Law. This legal void reveal itself as a gap to defend protect those who protect the land and natural resources. To skip this obstacle it is necessary, first, to analyze the later developments in this subject matter as found in the Agreement of Escazu, and then it is also necessary to study an alternative type of logic. Finally, the conclusion is that, through abductive inference, 9th article interpretation by the judiciary can solve the struggle of environmental defenders’ in access to justice. © 2020 Editora Dom Helder. All rights reserved.